PENGARUH PENGERTIAN PSIKOLOGIS KOMUNITAS MEREK PADA REKOMENDASI MEREK DIMEDIASI NILAI PERSEPSIAN - Litha Aulia Kartika; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
his study aims to determine the psychological sense of brand community on brand recommendations mediated by the perceived value of the football club Persis Solo. Data collection was carried out through a questionnaire that was distributed to members of the club supporters Persis Solo. The sampel of this research is 200 members of the club supporters Persis Solo. The sampling technique used was pur posive sampling. These were analyzed using SPSS analysis. The result in this study indicate that all hypotheses are supported. The psychological sense of the brand community has a positive effect on brand recommendations. The psychological sense of the brand community has a positive effect on perceived value. Perceived value has positive effect on brand recommendation. Perceived value perfectly mediating the relationship between the psychological sense of brand community and brand recommendation. Logistic regression analysis method gives the result that the perceived value has a perfect mediating role in this study. Means that the perceived value antecedents consisting of product benefits, service benefits and monetary costs require a perceived value as an evaluation of someone to consider buying a product.